(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the infection status in patients with acute-on-chronic liver failure (ACLF). Subjects and Methods: An observational study was conducted on 80 ACLF patients treated at the Intensive Care Center, Bach Mai Hospital, during the period 2020-2025. Results: Mean age 52.5 ± 12.1 (21-79), male gender (86.3%). Overall infection rate (68.8%). Bacterial infection (31.3%), fungal infection (5%). Hospital infection (94.5%). The most common types of infection are lung (53.8%), blood (16.3%). The main causes of blood and lung infections are gram-negative bacteria, while common causes of urinary tract infections are gram-positive enterococci. Ceftazidime/avibactam is still effective for K. pneumonia and P. aeruginosa; E. coli is still sensitive to piperacillin/tazobactam, aminosid and carbapenem; A. baumannii is resistant to most commonly used antibiotics in Vietnam; many bacteria are still sensitive to amikacin and gentamycin; Gram-positive bacteria are still sensitive to vancomycin and linezolid. Conclusion: Infections in ACLF patients are high, mainly hospital-acquired infections with common infections being lung and blood. Gram-negative bacteria are the main cause, in which K. pneumoniae, P. aeruginosa are still susceptible to ceftazidime/avibactam, E. coli is still susceptible to piperacillin/tazobactam, aminosid and carbapenem, while A. baumannii is resistant to most commonly used antibiotics. Gram-positive bacteria are still highly susceptible to vancomycin and linezolid